2020
DOI: 10.1136/bmjresp-2020-000695
|View full text |Cite
|
Sign up to set email alerts
|

Education and pneumonia mortality: a trend analysis of its inequalities in Colombian adults

Abstract: ObjectiveTo explore the existence and trends of social inequalities related to pneumonia mortality in Colombian adults using educational level as a proxy of socioeconomic status.MethodsWe obtained individual and anonymised registries from death certificates due to pneumonia for 1998–2015. Educational level data were gathered from microdata of the Colombian Demography Health Surveys. Rate ratios (RR) were estimated by using Poisson regression models, comparing mortality of educational groups with mortality in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In a study located in Colombia, it was found that the risk of dying was significantly higher among the lower-educated adults aged 25 and above for both men and women, with a relative risk of 2,34 (95% CI 2,32 -2,36) for primary education. 18 Another study in Brazil found that the proportion of hospital pneumonia admissions relative to the overall admissions is greater in cities with higher levels of social inequality (p < 0,05). 19 However, the slight difference in lower education definition may contribute to the difference in findings.…”
Section: Discussionmentioning
confidence: 97%
“…In a study located in Colombia, it was found that the risk of dying was significantly higher among the lower-educated adults aged 25 and above for both men and women, with a relative risk of 2,34 (95% CI 2,32 -2,36) for primary education. 18 Another study in Brazil found that the proportion of hospital pneumonia admissions relative to the overall admissions is greater in cities with higher levels of social inequality (p < 0,05). 19 However, the slight difference in lower education definition may contribute to the difference in findings.…”
Section: Discussionmentioning
confidence: 97%
“…The highest pneumonia burden is suffered by the elderly, with male sex predominance [ 5 7 ]. Pneumonia risk factors include low socioeconomic status, smoking, excessive alcohol consumption, chronic respiratory disease, chronic heart, liver and kidney diseases, autoimmune conditions, diabetes or haematological conditions, which are especially described among the elderly [ 8 15 ]. However, risk profiles for pneumonia among the young and working-age adult populations are not equally assessed [ 13 , 16 – 20 ].…”
Section: Introductionmentioning
confidence: 99%